Stroke survivors', caregivers' and GPs' attitudes towards a polypill for the secondary prevention of stroke: a qualitative interview study. Issue 5 (13th May 2016) - Jamison, James; Graffy, Jonathan; Mullis, Ricky; Mant, Jonathan; Sutton, Stephen
Abstract : Objectives: To understand the perspectives of stroke survivors, caregivers and general practitioners (GPs) on a polypill approach, consisting of blood pressure and cholesterol-lowering therapies, with or without aspirin, for the secondary prevention of stroke. Methods: A qualitative interview study was undertaken in 5 GP surgeries in the East of England. 28 survivors of stroke/transient ischaemic attack (TIA) were interviewed, 14 of them with a caregiver present, along with a convenience sample of 5 GPs, to assess attitudes towards a polypill and future use. Topic guides explored participants attitudes, potential uptake and long-term use, management of polypill medication and factors influencing the decision to prescribe. Data were analysed using a grounded theory approach. Key themes are presented and illustrated with verbatim quotes. Results: The analysis identified 3 key themes: polypill benefits, polypill concerns and polypill lessons for implementation. Stroke/TIA survivors were positive about the polypill concept and considered it acceptable in the secondary prevention of stroke. Perceived benefits of a polypill included convenience resulting in improved adherence and reduced burden of treatment. Caregivers felt that a polypill would improve medication-taking practices, and GPs were open to prescribing it to those at increased cardiovascular risk. However, concerns raised included whether a polypill provided equivalent therapeutic benefit, side effects through combining medications, consequences of non-adherence, lack of flexibility in regulating dosage, disruption to current treatment and suitability to the wider stroke population. Conclusions: Participants acknowledged potential advantages in a polypill approach for secondary prevention of stroke; however, significant concerns remain. Further research on the efficacy of a polypill is needed to reassure practitioners whose concerns around inflexibility and treatment suitability are likely to influence the decision to prescribe a polypill for secondary prevention of stroke. Acceptability among survivors, caregivers and GPs is likely to determine the uptake and subsequent use of a polypill in the future.